(untitled) (American Journal of Islam and Society, 2020)
The Ḥanbalī jurist and theologian Ibn Qayyim al-Jawziyya (d. 751/1350) has attained something of a celebrity nimbus in recent years. Since the publication of an edited volume entitled A Scholar in the Shadow: Essays in the Legal and Theological Thought of Ibn Qayyim al-Ğawziyyah1 in 2010 several studies of his thought and works have been published in both monograph and article form, and many of his texts have been translated into English and other languages.2 The shadow to which the aforementioned title refers, that of Ibn al- Qayyim’s teacher Ibn Taymiyya, is still present in the reception of Ibn al-Qayyim’s thought and work, but he is increasingly being seen as an original and influential figure in his own right. The attention that he now enjoys in English-speaking academic circles echoes his immense popularity in the Islamic world with a wide range of readers. Download